Peningkatan Kemampuan Membaca Permulaan Dengan Menggunakan Metode Bermain Flash Card Subaca - Sari, Rika Partika; Suryani, Novi Ade; Imran, Ranny Fitria (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2018)
This study aims to improve the ability to read the beginning of students by using the SUBACA Flash Card method for children in group B PAUD AL-ANISA Bentiring, Bengkulu City. This type of research is Classroom Action Research using two cycles, where each cycle is carried out in three meetings. Methods of collecting data in the form of observation and documentation. The results showed that there was an increase in reading the beginning of the child in each cycle with the average percentage of success in Cycle I was 47% and in the second cycle was 82.8%. It can be concluded that the method of playing SUBACA Flash Card is quite effective to be used to improve the ability to read the beginning in the children of group B PAUD AL-ANISA Bentiring, Bengkulu City.